EVALUASI MANAJEMEN PELAYANAN PUBLIK - Arliliwati, Zaili Rusli, Febri Yuliani (Universitas Riau, 2019)
Evaluation of Public Service Management. The approach or type of research isqualitative. This study aims to determine how the public service management of PDAM Tirta Siak.Research informants are directors, staff of human resources, subscription relationships,transmission and customers. Data collection techniques are interviews, observation anddocumentation. Data analysis starts from data reduction, classification and drawing conclusions.The results of this study found that the public service management of PDAM Tirta Siak PekanbaruCity was not carried out optimally.